Out‐of‐hospital, non‐invasive, positive‐pressure ventilation for acute dyspnea. Issue 6 (4th November 2021) - Walter, Daniel C.; Chan, Hei Kit; Crowe, Remle P.; Osborn, Lesley; Jarvis, Jeffrey; Wang, Henry E.
Abstract: Background: Emergency medical services (EMS) patients with acute dyspnea require prompt treatment. Limited data describe out‐of‐hospital dyspnea treatment with non‐invasive, positive‐pressure ventilation (NIPPV), including continuous positive airway pressure (CPAP) or bi‐level positive air pressure (BPAP). We sought to determine the course and outcomes of out‐of‐hospital acute dyspnea patients treated with NIPPV. Methods: We analyzed retrospective data on 1289 EMS agencies from the ESO Data Collaborative (ESO, Inc., Austin, TX) between January and December 2018. We defined acute dyspnea as adults with an initial respiratory rate ≥ 30 breaths/min (bpm), with a primary or secondary EMS subjective impression of a respiratory condition, who received oxygen and/or a respiratory medication and had 2 or more recordings of respiratory rate (RR). We excluded patients with trauma and those with altered mental status. We identified cases receiving care with and without NIPPV. The primary outcome was change in respiratory rate (RR), censored at 90 minutes of treatment. We compared baseline characteristics between NIPPV and non‐NIPPV patients. We compared RR changes between NIPPV and non‐NIPPV patients at 20 and 40 minutes of treatment. Using mixed linear, fractional polynomial, and multiple spline models, we examined the association of out‐of‐hospital NIPPV with overall change in RR. Secondary outcomes included whether the patient received advanced airway treatment (intubation, supraglottic airway device, and/or cricothyroidotomy). Results: We analyzed 33, 585 EMS encounters for patients with acute dyspnea, including 8, 750 (26.1%) NIPPV and 24, 835 (73.9%) non‐NIPPV encounters. Median treatment duration was similar between NIPPV and non‐NIPPV (23.3 minutes vs 23.6 minutes, rank‐sum P = 0.266). Common concurrent treatments included albuterol (NIPPV, 48.8%; non‐NIPPV, 46.2%), ipratropium bromide (27.9%, 24.8%), and methylprednisolone (24.9%, 18.5%). At 20 minutes, mean RR change was slightly lower for the NIPPV group than non‐NIPPV; −6.0 versus −6.8 breaths/min. At 40 minutes, mean RR change was similar between NIPPV and non‐NIPPV groups; −7.7 versus −7.9 breaths/min. On linear mixed modeling adjusted for age, sex, incident location, race, ethnicity, agency type, initial RR, and medication use, NIPPV was associated with a smaller RR decrease across time than NIPPV; [NIPPV × time] interaction P < 0.001. Out‐of‐hospital advanced airway placement (endotracheal intubation or supraglottic airway insertion) was higher for NIPPV than non‐NIPPV group (2.3% vs 1.3%, odds ratio = 2.23, 95% confidence interval = 2.01–2.47). Conclusions: NIPPV has been proven to be an effective treatment for out‐of‐hospital patients experiencing acute dyspnea through prior studies. Our findings provide detailed insight into characteristics and use of NIPPV and highlight the commonality of this treatment modality with use in over 1 in 4 patients in respiratory distress.